Mental Health Literacy and Professional Psychological Help-Seeking Attitudes Among Primary Healthcare Workers: The Mediating Role of Social Support and Mental Illness Stigma - He X; Chen S; Zhang Q; He S; Yang L; Ma J (Risk Management and Healthcare Policy)
Xuntao He,1,* Shibin Chen,2,* Quyi Zhang,1 Shu He,2 Lin Yang,1 Jun Ma1 1School of Public Health, Chongqing Medical University, Chongqing, 401331, People’s Republic of China; 2Chenjiaqiao Hospital, Chongqing, 401331, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Ma, School of Public Health, Chongqing Medical University, No. 61 University Town Middle Road, Shapingba District, Chongqing, 401331, People’s Republic of China, Tel +86-13983086198, Email majun@cqmu.edu.cnBackground: Research highlights poor mental health among healthcare workers, but limited attention has been given to the mental health literacy and professional psychological help-seeking attitudes of primary healthcare workers.This study investigates the relationship between primary healthcare workers’ mental health literacy and their attitudes toward professional psychological help-seeking. It also explores the chain mediating roles of social support and mental illness stigma in this relationship.Methods: We conducted the study among primary healthcare workers in Shapingba District, Chongqing, China. The study utilized demographic questionnaires, the Multiple Mental Health Literacy Scale, Social Support Rating Scale, Perceived Devaluation-Discrimination Scale, and Attitudes Toward Seeking Professional Psychological Help Scale. We applied Pearson correlation, multiple linear regression, and structural equation modeling (SEM) for data analysis.Results: Correlation analysis revealed positive associations between mental health literacy and help-seeking attitudes, while stigma negatively impacted these attitudes. The regression analysis demonstrated that mental health literacy, social support, and mental illness stigma significantly influenced attitudes toward professional psychological help-seeking, with the adjusted R square being 0.402. Specifically, social support and stigma acted as partial mediators in the relationship between mental health literacy and help-seeking attitudes. SEM confirmed a significant chain mediation effect, with social support and stigma jointly mediating the link between mental health literacy and help-seeking attitudes, explaining 27.46% of the variance.Conclusion: This study underscores the critical role of mental health literacy, social support, and mental illness stigma in shaping primary healthcare workers’ attitudes toward professional psychological help-seeking. Strengthening these factors can enhance their mental health outcomes and encourage more proactive help-seeking behavior. Implementing targeted interventions in training programs to reduce stigma and promote social support could improve help-seeking behaviors and overall mental health within healthcare settings.Keywords: primary healthcare worker, mental health, social support, mental illness stigma, professional psychological help-seeking attitudes